Hubungan Academic Burnout dengan Self-Esteem Siswa Kelas XI di SMA Malahayati - Shafira Azzahra; Siti Hajar (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Academic burnout is a psychological condition frequently experienced by students due to excessive academic demands. High academic pressure may lead to emotional exhaustion, decreased learning motivation, and reduced academic engagement. This study aimed to examine the relationship between academic burnout and self-esteem among eleventh-grade students at SMA Malahayati. This research employed a quantitative approach with a correlational design. The participants consisted of 123 students selected through simple random sampling. Data were collected using self-esteem and academic burnout scales, and analyzed using Pearson Product Moment correlation after meeting the assumptions of normality and linearity. The results revealed a significant negative relationship between self-esteem and academic burnout, with a correlation coefficient of -0.373 and a significance value of 0.000 (p < 0.05). These findings indicate that students with higher self-esteem tend to experience lower levels of academic burnout. In conclusion, self-esteem plays an important role in reducing academic burnout among students. Therefore, efforts to enhance students’ self-esteem may contribute to improving their academic well-being and reducing burnout levels.